GC-MS analysis of Iraqi Silybum marianum Flowers, Leaves and Seeds Extracts - Rasha Eldalawy; Wasan Abdul kareem; Widad M K Al-Ani (College of Pharmacy / Mustansiriyah University, 2022)
Iraqi land is rich with medicinal plants and Iraqi people trust using herbals as treatments since ancient times, one of these important wild medicinal plants is Silybum marianum, which is known as Milk thistle. It has a long history in Greek and Arabian medicine as a liver tonic which has been confirmed by scientific in vivo/ in vitro study and made the plant in the top of medicine that can regenerate liver tissues and cure various liver diseases. The aim of this study is to investigate the active constituents in the seeds, leaves and the flowers of Iraqi Silybum marianum, identification  have been done by GC-MS instrument after the extraction process by hexane then ethanol as a solvent in the Soxhlet apparatus, An important compounds has been detected such as phytosterol, catechin, terpenes, fatty acids, fatty alcohol, and  monosaccharide,  in different concentration in the parts of the plants.